ANALYSIS OF THE INFLUENCE OF FINANCIAL PERFORMANCE ON STOCK RETURNS: AN EMPIRICAL STUDY IN THE BANKING SECTOR - Yuni Astuti (Count : Journal of Accounting, Business and Management, 2025)
This study aims to empirically examine the effect of financial performance indicators— specifically Return on Assets (ROA), Return on Equity (ROE), and Earnings per Share (EPS)— on stock returns in publicly listed banking companies in Indonesia during the post-pandemic recovery period (2020–2024). Using a quantitative approach with panel data regression models, including Fixed Effect and Random Effect Models, the study analyzes data obtained from audited financial statements and stock price movements published on the Indonesia Stock Exchange (IDX). The Hausman test results support the Fixed Effect Model as the most appropriate. Empirical findings reveal that ROE has a significant positive effect on stock returns, while ROA and EPS do not exhibit statistically significant influence. These results suggest that investors prioritize equity efficiency over earnings or asset utilization when assessing banking performance in uncertain economic conditions. The novelty of this research lies in its focus on the post-COVID- 19 economic context, its sector-specific approach, and the use of updated analytical methods to reevaluate traditional valuation indicators. Moreover, the study contributes to global financial literature by demonstrating that widely accepted indicators such as EPS may not consistently predict stock performance in emerging markets. In conclusion, ROE remains the most reliable indicator for predicting investor response in Indonesia’s banking sector, indicating a shift in market behavior that has both academic and practical implications. These insights are useful for investors, analysts, and regulators seeking evidence-based valuation frameworks in developing economies.